On the Magic of Law - Laurent de Sutter (Law Text Culture, 2017)
This essay focuses on a forgotten and ill-reputed category, long used by anthropologists and historians to describe the origins of law: the category of “magic.” At the end of the 19th century, many scholars found in the idea of “magic” something that could explain why some sort of a necessity could be attached to certain actions, paroles or rituals from which concrete, practical effects were expected in “primitive” societies. “Magic” was a concept embodying a complete theory of performance, and of the necessity of the consequences produced by this performance, that seemed to some of those scholars capable of explaining why necessity and performance were also legal features. Yet, after World War II, the positivist school of legal historians chose to discard this explanation, and to forget all about the possible links between law and magic. By re-reading the work of Paul Huvelin, a forgotten French legal historian close to the circles of Emile Durkheim, I would like to claim that this gesture was rather a form of foreclosure – foreclosure of the fact that law might very well be the last form of magic in a world that refuses to admit its existence. Of course, the whole question is: Which magic? How magic? Why magic? These are the questions that the essay tries to answer.